New headway English course intermediate workbook - Soars, Liz (Oxford University Press, 1996)
Features include: the 'Test your grammar' section at the beginning of every unit challenges students' knowledge of the language; grammar questions involve students in language analysis, which is practised through a range of exercises; and the 'Postcript' section looks at everyday idiomatic English and the grammar of spoken English